MED1101: A new dialdehydic compound regulating P2×7 receptor cell surface expression in U937 cells. (15th July 2013) - Muzzachi, Stefania; Blasi, Antonella; Ciani, Elena; Favia, Maria; Cardone, Rosa A.; Marzulli, Domenico; Reshkin, Stephan J.; Merizzi, Giulia; Casavola, Valeria; Soleti, Antonio; Guerra, Lorenzo
<x xml:space="preserve">Abstract</x> We demonstrated that the novel dialdehydic compound, MED1101, may act as a key modulator of monocyte inflammatory response. This occurs through induction of P2X7R internalisation, followed by impairment of the P2X7R‐dependent intracellular signalling transduction, as suggested by inhibition of Ca2+ influx, MAPK phosphorylation, production of pro‐inflammatory chemokines and monocyte migration/transmigration. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>